Mathematical Self-Efficacy Among Senior High School Students At Man 1 Aceh Utara - Zainal, Rohantizani; Nuraina Nuraina (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
Students with strong mathematical self-efficacy are better equipped to handle challenges in various aspects of life. This study was aimed to assess the self-efficacy of students in mathematics at MAN 1 Aceh Utara, Aceh Utara, during the 2023/2024 academic year. A qualitative research method was employed, with data collected through a questionnaire. The participants were 60 grade XI students. The results revealed that 12 students (20%) demonstrated high self-efficacy, 34 students (56.67%) exhibited moderate self-efficacy, and 14 students (23.33%) had low self-efficacy. The overall average self-efficacy score was 68.38%, placing grade XI students of MAN 1 Aceh Utara in the moderate self-efficacy category.